Serviciile sociale prestate de biserica ortodoxă în conlucrare cu instituțiile statului [Articol] - Botea, Veaceslav (CEP USM, 2024)
The Orthodox Church, as a religious institution, is not limited only to the dimension of worship, but also extends its involvement in the social field, responding to the diverse needs of society. In a context where problems such as poverty, marginalization and lack of access to basic resources become more and more acute, the social services offered by the Orthodox Church become an essential factor in supporting those affected. Social Context and Community Needs: To fully understand the contribution of the Orthodox Church, we must analyze the social context in which it carries out its social activities. The diverse needs of local communities, as well as the challenges faced by vulnerable individuals, will underpin our argument. In the 21st century, with the complex challenges of contemporary society, the Orthodox Church is becoming increasingly present in the sphere of social services, surpassing its traditional spiritual mission, the contribution of the Orthodox Church in providing social services, highlighting its impact on local communities.
SOCIAL SERVICES PROVIDED BY THE ORTHODOX CHURCH IN COOPERATION WITH STATE INSTITUTIONS
Keywords: analysis; church; community; challenge; social